2017
DOI: 10.22623/ijapsa.2017.3027.jakpa
|View full text |Cite
|
Sign up to set email alerts
|

GROWTH PERFORMANCE OF VIGNA RADIATA(L.)R.Wilczek UNDER HYDROPONIC SYSTEM

Abstract: Abstractst days in Natural system and plastic pots. Using of plastic pots in hydroponic system had better result. Conc.II Nutrient solution (medium level nutrient content) using plants had better growth as well as the plats had better nutrient content. Hydroponic system have a better result when compared to natural system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…High phenotypic growth and quality of carrot were obtained in a soilless system under a greenhouse . Studies on Chinese cabbage in substrate growing media of rice husk, perlite, and peat moss in pot culture at Pusan National University, Miryang campus, South Korea, showed that the vegetative growth of Chinese cabbage was higher in peat moss than in rice husk and perlite . Substrate growing media in the proportion of 150 g coir dust and 300 g soil + 100 g sand facilitated germination of green gram in a container in a glasshouse…”
Section: Substrates or Growing Media Used In Soilless Crop Productionmentioning
confidence: 99%
“…High phenotypic growth and quality of carrot were obtained in a soilless system under a greenhouse . Studies on Chinese cabbage in substrate growing media of rice husk, perlite, and peat moss in pot culture at Pusan National University, Miryang campus, South Korea, showed that the vegetative growth of Chinese cabbage was higher in peat moss than in rice husk and perlite . Substrate growing media in the proportion of 150 g coir dust and 300 g soil + 100 g sand facilitated germination of green gram in a container in a glasshouse…”
Section: Substrates or Growing Media Used In Soilless Crop Productionmentioning
confidence: 99%